Workplace Spirituality Making a Difference - Altman, Yochanan; Neal, Judi; Mayrhofer, Wolfgang (Management, Spirituality and Religion, 2022)
A state-of-the-art overview of the field of management, spirituality and religion, comprising concise chapters written by experts in the sub-fields and edited by recognized leaders in the field of management, spirituality and religion.